Generation cost reduction through optimal allocation of energy transactions by bilateral quantity adjustments with corresponding penalties - Jimenez, Marcial Brummel J.
An electricity market is established to create a fair, transparent and reliable trading environment and encourage competition that will lead to a cheaper cost of electricity. In this set-up it is very important that the distribution companies allocate their purchases of energy in the spot market and in the bilateral contract in the most economic manner. This study developed a methodology for re-scheduling the economic purchases of energy in the spot market and in the bilateral contract through bilateral contract adjustments with corresponding penalties. The methodology minimizes the total monthly energy cost by optimally allocating the energy purchases between the spot market and bilateral contracts. Likewise, it considers the effect these changes to the generation companies' contracted sales. The corresponding penalty cost is based on the equilibrium point wherein the distribution company's savings matches the increase in the generation companies' sales. The methodology is applied to the settlement processes as defined in the Philippine Wholesale Electricity Spot Market (WESM) Rules and Price Determination Methodology (PDM) in which bilateral contract quantity is used as decision variables in the linear programming. The new schedules of bilateral contract quantities which are beneficial to both the generating and distribution companies yielded a cheaper energy purchases without breaching the contracts. This will eventually lead to lower generation costs for the consumers.